The Optimal Level of International Reserves: The case of Algeria - Rahabi, Anys (2010)
Algeria has seen a surge in its international reserves over the past few years. However, most of this growth is originated by the important increase in oil prices Algeria’s economy is widely dependent vis-à-vis hydrocarbon’s prices due to a low development and diversification of its economic activities. This economy is thus very exposed to external shocks and should prevent against bankruptcy and ensure sufficient equity to import goods and services during these adverse periods. In our study, we first describe certain conventional measures of reserves adequacy and apply them to Algeria. We then analyse Algeria’s historical data in order to determine the periods in which sudden-stops have occurred. Afterwards, we determine Algeria’s foreign reserves levels using an optimizing model based on Jeanne and Ranciere (2006) approach. As an extension of this model, we represent the effect of the dependence of the national economy vis-à-vis hydrocarbons as a major factor affecting the probability of a sudden-stop. As a result, our evaluation allows us to conclude that Algeria’s foreign reserves are largely sufficient since 2002 and could allow cope with the most severe capital account disturbances.